Determinants of Village Financial Fraud: The Mediating Role of Accountability Practices - Halkadri Fitra; Rino Dwi Putra; Dewi Pebriyani; Diva Putri Meisya (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the determinants of village financial fraud by integrating individual, organizational, and governance perspectives, with a particular focus on the mediating role of accountability. Methodology: This study employed a quantitative explanatory approach to examine the causal relationships. Data were collected through structured questionnaires distributed to village government officials, with a population of 440 respondents and a purposive sample of 210. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess the direct and indirect relationships among the variables. Results: The findings show that internal control systems, competence, and the morality of officials significantly reduce fraud in village financial management, while performance pressure has no significant effect. In addition, internal control systems, performance pressure, competence, and the morality of officials significantly influence accountability. Accountability practices were also found to mediate the effects of internal control systems, competence, and the morality of officials on fraud reduction, but did not mediate the effect of performance pressure on fraud reduction. Conclusions: This study concludes that fraud prevention in village governance requires not only strong control systems and competent human resources but also the effective institutionalization of accountability practices as a governance mechanism. Limitations: This study is limited by its cross-sectional design and reliance on self-reported data, which may affect causal interpretation and introduce potential response bias in the results. Contributions: This study contributes to the literature by proposing an integrative multilevel model that positions accountability as a mediating mechanism, thereby providing a more comprehensive understanding of fraud prevention in the public sector, particularly in the context of village governance.